The preliminary ethnobotanical study of medicinal plants in Usak (Turkey) - EMRE, GİZEM (MARMARA UNIV, FAC PHARMACY, 2017)
This study was made to reveal the plants used as traditional folk medicine in Usak in 2013. The specimens of the plants used as folk remedies have been collected and the information about the local names, the part(s) used, the ailments treated, the therapeutic effect, the preparation, the methods of administration, and the duration of treatment were recorded. The plant specimens are kept in the Herbarium of the Faculty of Pharmacy, Marmara University. As a result of identification of the plant specimens, 38 species, used as a traditional folk medicine in Usak, have been determined. According to the majority of the plants which have similar usages, the plants were mostly used for gastrointestinal system diseases, respiratory system diseases and urinary system diseases.
Keywords: Ethnobotany; Folk medicinal plants; Usak; Turkey; WEST ANATOLIA; TRADITIONAL MEDICINE; FOLK MEDICINE; MANISA; BALIKESIR; MUGLA